Studi dan peningkatan fitur pada aplikasi Al-Qur'an digital - hidayah, hikmatul (Maliki Interdisciplinary Journal, 2024)
The Qur'an is the divine word of Allah, containing miraculous qualities. It was revealed to the Prophet Muhammad SAW through the angel Gabriel, preserved in the mushaf from Surah Al-Fatihah to Surah An-Nas, transmitted through a continuous chain (mutawatir), and its recitation is an act of worship. With its unique attributes and grandeur, reading and practicing the Qur'an brings boundless blessings and grace from Allah. Whether or not one understands its meanings, reciting the Qur'an remains an essential form of worship. This article will explore the dynamics of learning and developing the digital Qur'an. This study adds to our understanding of Qur'an learning and development in the modern era, which faces significant challenges and transformations due to digital technology. As the learning process evolves across generations, there is a need for strategies that align with the advancement of digital and information technology